Synthesis and characterization of stable dicarboxylic pegylated magnetite nanoparticles - Gil, Sara (2013)
The coating of implantable nano- or micro-objects with polyethylene glycol (PEG) enhances its biocompatibility and biodistribution. Herein, we describe a new protocol that enhances and maintains MNPs stability in biological media, simulating multiple conditions to which they would be subjected in the human body. Magnetite nanoparticles (MNPs) prepared via a facile way at room temperature by co-precipitation reaction, were coated with dicarboxylic polyethylene glycol (DCPEG) via covalent bonds. The surface of the nanoparticles was first coated with 3-aminopropyl trimethoxysilane by a silanization reaction and then linked with DCPEG of different molecular weight (Mw=5000, 10,000 and 20,000 g mol−1). The uncoated magnetite nanoparticles, with an average size of 20 nm, exhibited superparamagnetism, high saturation magnetization and a negative surface charge (with a zeta potential value of −40 mV). Increase of Mw enhances the colloidal stability of MNPs and makes them more suitable to tolerate high salt concentrations (1M NaCl) and wide pH (from 5.5 to 12) and temperature ranges (24 °C to 46 °C). The results indicate that magnetite nanoparticles coated with DCPEG with Mw=20,000 have improved properties over their counterparts, making them our best choice for biomedical studies.